(untitled) (Journal of Musikot Campus, 2025)
The aim of this study to explore the determinants of food security, focusing on the variables that influence households’ access to adequate and nutritious food. A deductive strategy and descriptive and causal-comparative study design were utilized. Non-probability convenience sampling technique was utilized for data collection among 385 members of households of Rolpa District, Nepal. Descriptive analysis was utilized for assessing the central tendencies of variables based on data from Likert scale surveys with a majority base. Pearson correlation and multiple linear regression models were utilized for conceptualizing the determinants of food security. The results showed that income, employment status, access to financial services, education, gender dynamics, climate conditions, land access, and agricultural productivity all have a positive and significant impact on food security. In contrast, household size was found to have a negative and significant impact on food security. And it was also found that the independent variables explained about 73.50 percent of food security variation. This study concludes that economic, social, and environmental factors are powerful tools for bringing effective positive changes to the food security of the households. Understanding these determinants in crucial for policymakers and development practitioners working to enhance food security across different regions.